Factors Affecting the Spatial Resolution in 2D Grating–Based X-Ray Phase Contrast Imaging - Tao, Siwei; He, Congxiao; Hao, Xiang; Kuang, Cuifang; Liu, Xu (Frontiers in Physics, 2021)
X-ray phase contrast imaging is a promising technique in X-ray biological microscopy, as it improves the contrast of images for materials with low electron density compared to traditional X-ray imaging. The spatial resolution is an important parameter to evaluate the image quality. In this paper, simulation on factors which may affect the spatial resolution in a typical 2D grating-based phase contrast imaging system is conducted. This simulation is based on scalar diffraction theory and the operator theory of imaging. Absorption, differential phase contrast and dark-field images are retrieved via the Fourier transform method. Furthermore, the limitation of the grating-to-detector distance in the spatial harmonic method is discussed in detail.